Technological rationality and educational research - Nobile, Elena (Formazione & insegnamento, 2015)
The starting point which this article begins from concerns the rationality that characterizes our living in the world, that is to say the technological rationality. Through some philosophers’ contribution I will attempt to highlight how the relationship man-machine is completely overturned with the rising of modernity: the Man surrenders to what he himself generated. Therefore it rises what we can define as an educational emergency, which is the necessity of rethinking about the Human in an age when everything seems to need to be technically articulated. A first area where you can spot the outcomes of this logic is that of the educational research. So, through an incursion in the ‘900 epistemology, I shall try to highlight the criticalities of the quantitative methodology, as much as the criticalities of the qualitative one with the aim of proposing a “third way”, way capable of catching the specificity of the “object” (if education can be thus conceived) which our reflection is developed on.